Educação e convivência social na terceira idade: percepção de mudanças na qualidade de vida dos participantes da Universidade aberta à terceira idade da UNIFESP campus Baixada Santista - Martins, Rita de Cassia Cabral de Campos [UNIFESP] (2016)
This study aimed to identify and understand the relationships between education, social interaction and the perception of quality of life in old age. It is an exploratory research, of qualitative and quantitative approaches about the participation of the elderly at the University of the Third Age at UNIFESP- Baixada Santista (UTA/BS) in 2015 and the perception of the improvement in their quality of life. The subjects were 13 participants of the UTA/ BS, 15,85% of the UTA/BS students over 65 years of age, who were randomly chosen from its two groups (Silva Jardim and Zona Noroeste). The quantitative survey was carried out by the application of the SF-36 questionnaire, its results being statistically calculated by the Statistica 12 program, t-Student test p?0.05 (*) significance level. As a qualitative instrument, semi-structured interviews were conducted with the same subjects, and the data analyzed through the content analysis/thematic analysis technique. Both instruments were applied in two stages, at the beginning and the end of the UTA/BS school year. The results of the SF-36 showed no significant differences between the groups in the starting and ending instances, except for the variable Vitality (V) which increased in SJ group and in the total sample. Regarding the qualitative results, the data pointed to perceived changes concerning the education and social interaction?s role in the perception of improvement in the quality of life, for both groups and the total sample. In conclusion, the participation in the UTA/BS groups has promoted the perception of positive changes in the quality of life of the participants.